Effects of knowing the task duration on players` pacing patterns during soccer small-sided games - Ferraz, R.; Gonçalves, B.; van den Tillaar, R.; Jiménez Sáiz, S.; Sampaio, J.; Marques, M. C. (Journal of Sports Sciences, 2018)
The aim of this study was to identify the influence of prior knowledge of exercise duration on players` pacing patterns during soccer small-sided games. Twenty semi-professional male soccer players participated in this study. In the first game scenario, players were not informed how long they would be required to play the small-sided game and the activity was terminated after 20 min (Unknown Condition). In the second game scenario, players were told that they would play the small-sided game for 10 min, but immediately after completing the 10-min game, they were asked to complete another 10 min (Partially Condition). In the third game scenario, players were instructed that they would play the small-sided game for 20 min and then they completed the 20-min game (Known Condition). The results presented a tendency of higher values in all performance variables in the [0'-10'] min compared with the [10'-20'] min. As the players` previous knowledge about the tasks duration increased, the performance between two moments tended to be similar. Considering the entire 20-min game duration, the Partially Condition of the exercise was the most demanding condition. In conclusion, the knowledge of shorter durations of the exercise seems to lead to an increase of exercise duration demand, and longer exercise durations possibly tend to decrease differences between full knowledge and not knowing the exercise duration.